Digital Supplementary Future Tense Material Development Using Quizizz Application for First Year Students - Made Suharwipa; I Gusti Ayu Lokita Purnamika Utami; Made Hery Santosa (JPP (Jurnal Pendidikan dan Pembelajaran), 2022)
This study aimed to determine how the procedures to develop digital supplementary future tense material through Quizizz for first year level promoted by Richey and Klein's (2005) Design and Development research (DnD) approach, as well as how the product's quality evolved. Design, development, and evaluation were the three primary steps of this study. A descriptive quantitative analysis was performed to analyze the data, that explained in the distribution of scores and categories of rating scales that were determined using instrument validations. Product validation scores for content evaluation are 98.1% and 96.3%, respectively, while media assessment results are 87.2% and 85.4%. Based on findings, the digital supplementary future tense material developed with Quizizz was designed to be used in the learning process at freshman level.